ADRENAL INSUFFICIENCY IN PAKISTANI HIV INFECTED PATIENTS - Afreen, Bahjat; Khan, Khurshid Ahmed; Riaz, Amna (Journal of Ayub Medical College Abbottabad, 2017)
Background: Adrenal insufficiency (AI) is the most common endocrine complication among patients with AIDS/HIV infection and there are number of causes of AI in HIV patients. Human immunodeficiency virus directly as well as indirectly destroys adrenal glands. The estimates of its prevalence and severity vary. AI is the most life threatening but readily correctable endocrine complication that occurs in persons with HIV infection. This study was carried out to determine the frequency of Adrenal Insufficiency in HIV patients and their clinical features as proper diagnosis and timely treatment have been shown to improve quality of life and long-term mortality in AIDS patients. Methods: It was a cross sectional survey conducted at HIV clinic and Jinnah Allama Iqbal Institute of Diabetes and Endocrinology, Jinnah Hospital Lahore. Sixty-four HIV positive patients, both male and female, aged above 15 years were included in the study. HIV patients who had recently taken steroids, ketoconazole or rifampicin, determined on history, were excluded from the study. The data was collected on a structured proforma and analysis was performed in SPSS-21.0. Frequency and percentages for adrenal insufficiency and its characteristics were calculated. Chi-square test was used with p<0.05 as statistically significant. Results: In this study, 9 (14.06%) HIV patients were diagnosed with adrenal insufficiency, male to female ratio was 3.5:1 and AI was found statistically significantly associated with fatigue (p<0.008) and weight loss (p<0.001). Conclusion: Adrenal insufficiency was high among the patients with HIV, it was not gender specific but it was found to be associated with fatigue and weight loss. Keywords: Adrenal insufficiency; HIV, Clinical features; Endocrinopathies